A Grammar of Shaowu A Sinitic Language of Northwestern Fujian - Ngai, Sing Sing (Sinitic languages of China ;, 2021)
This is the first comprehensive grammar of Shaowu, a Min language spoken in Shaowu city and its environs in northwestern Fujian province, China. The book offers first-hand linguistic data collected over four years in the field, now placed at the disposal of researchers and students working in language documentation, comparative linguistics and Sinitic typology. It can serve as a reference grammar for those interested in learning the Shaowu language, thereby helping to preserve it. In addition, the book provides insights into Shaowu's classification which has been widely debated, thus elucidating its genetic affiliation. 0 The book first presents Shaowu's geography, demography and history. It then profiles the language's phonology and lexicon, before providing a detailed description of its syntax, notably on its nominal, predicate, clausal and complex sentence structures, which are the focus of the book. 0 The typological profile of Shaowu is also treated with the conclusion that the language has Gan, Hakka, Mandarin and even some Wu overlays on its Min base. The Shaowu language serves an excellent example to illustrate the degree of hybridity a language can attain due to intensive language contact over time.